Understanding attainment in Religious Studies - Ehioze-Ediae, H (2023)
This small scale research project was designed to investigate barriers to students’ attainment in Religious Studies (RS), and how these barriers could be addressed to give students the best opportunities for success. A review of the literature was conducted which investigated the attainment gap, the aims of RS, and the issues that surround assessment in RS. Following this, the first phase of the research involved a focus group in collaboration with my colleagues. This was designed to gather teachers’ views of the barriers to learning in RS. Phase two of the research involved student interviews, which sought to establish what students find difficult about the subject. Subsequently, the intervention was delivered to a year 11 class where verbal feedback was given following a summative assessment. Findings indicate that students find RS difficult for two reasons: first, the vast amount of specific subject knowledge required, and second, lack of experiential knowledge and understanding of the religion studied. One method that could be used to address the challenge with subject knowledge is to implement 1:1 meetings to support revision. It is recommended that these are modelled on the intervention. However, some further research into teaching and learning techniques that would embed specific subject knowledge would be beneficial. Moreover, this is a small scale project and therefore it is difficult to claim that these findings are true for all of RS, however, the research methods could be replicated in other settings in order to corroborate this.